Prolonged uninterrupted sitting elevates postprandial hyperglycaemia proportional to degree of insulin resistance. Issue 6 (6th March 2018) - Dempsey, Paddy C.; Larsen, Robyn N.; Winkler, Elisabeth A. H.; Owen, Neville; Kingwell, Bronwyn A.; Dunstan, David W.
Abstract : Prolonged uninterrupted sitting is related adversely to cardiometabolic risk markers and postprandial hyperglycaemia, relative to sitting interrupted by regular brief activity breaks. However, whether the magnitude of hyperglycaemic responses to prolonged sitting is dependent upon the underlying degree of insulin resistance remains unclear. Data were pooled from 3 randomized cross‐over laboratory‐based trials ( n  = 62) that examined the postprandial blood glucose‐ and insulin‐lowering effects of prolonged sitting vs sitting interrupted by regular brief activity breaks in overweight/obese adults who had normal or impaired glucose metabolism (2 trials) or type 2 diabetes not treated by insulin (1 trial). Corrected for study effects, the magnitude of differences in postprandial glucose and insulin responses between the 2 conditions was significantly exacerbated with poorer baseline levels of fasting glucose, insulin and/or surrogate markers of β ‐cell function and insulin resistance. This suggests that those with higher underlying levels of insulin resistance may derive greater metabolic benefits from regularly interrupting prolonged sitting than their healthier counterparts. If these findings can be replicated, they may have implications for future targeting and optimization of physical activity/sedentary behaviour interventions in the prevention and management of type 2 diabetes.